Developing Writing Skills through Video-Based Contextual Teaching and Learning - Adawiyah, Rabiah; Usman, Sriati; Rita, Ferry; Suriaman, Aminah; Mahrum, Mochtar (STAIN Majene, 2023)
This research aims at developing writing skill of the tenth-grade students of MA Muhammadiyah Palu through Contextual Teaching and Learning video-assisted based. Another aims at student’s achievement in developing writing skill because the process of CTL video-assisted based. The subjects of this research were the students at the tenth grade of MA Muhammadiyah Palu that consisted of 15 students. This research was Classroom Action Research (CAR) covering plan, action, observation and reflection. This research was carried out into two cycles. The first cycle focused on explanation of the materials through the seven principles of CTL; 1. Constructivism, 2. Inquiry 3. Questioning, 4. Learning Community, 5. Modeling, 6. Reflection and 7. Authentic Assessment. The second cycle was focused on the examples of language features in procedure text. The data of this research were obtained from observation, field notes and writing test. The individual test results in cycle 1 showed that 40% of the students had not reached the criteria of success because they had not been able to write procedure text, while the results of the cycle 2 87% of the students showed that the implementation of the CTL video-assisted based was able to develop students’ writing skills. Students’ problems in writing procedure text can be diminished by implementing CTL video-assisted based.